Global lending conditions and international coordination of financial regulation policies - Kharroubi, Enisse (Journal of Financial Stability, 2023)
Using a model of strategic interactions between two countries, I investigate the gains to international coordination of financial regulation policies, and how these gains depend on global lending conditions. When one region – the core – sets global lending conditions, I show that coordinating regulatory policies makes the two regions better-off relative to the case of no cooperation. Global lending conditions set by the core are typically sub-optimal for the other region – the periphery –. To reduce this cost, the periphery can tighten its regulatory policy. Yet, in doing so, it fails to internalise a cross-border externality: when the periphery tightens its regulatory policy, agents in the core reduce cross-border borrowing, which tightens global lending conditions and hurts the periphery. The cooperative equilibrium can improve on this outcome. Both regions take into account the cross-border externality, leading to larger cross-border borrowing and less sub-optimal lending conditions for the periphery.